Transforming Scholastic Performance Through Spiritual Engagement in Islamic Education at Leading Rural Schools - Nurhalya, Hazira; Damni, Albertos (Dirasah: Jurnal Pendidikan Islam, 2025)
This study aims to explore the transformation of Scholastic Performance through Islamic Spiritual Engagement in a leading rural school. Using a quantitative method with a survey approach, this study involved 213 students as samples, which were taken through a simple random sampling technique. The results showed that religious activities, such as recitation, joining tahsin classes, joining the Qur'an tahfizh program, praying together, have a positive impact on learning motivation and can shape student character, which can contribute to improving students' Scholastic Performance. The findings suggest that there is a significant relationship between Spiritual Engagement and Scholastic Performance of students in excellent rural schools. The research shows that students who participate in religious activities tend to have better attitudes, including discipline, responsibility, and cooperation, all of which contribute to improving their Scholastic Performance.